2012
DOI: 10.1172/jci61953
|View full text |Cite
|
Sign up to set email alerts
|

G protein–coupled receptor 21 deletion improves insulin sensitivity in diet-induced obese mice

Abstract: Obesity-induced inflammation is a key component of systemic insulin resistance, which is a hallmark of type 2 diabetes. A major driver of this inflammation/insulin resistance syndrome is the accumulation of proinflammatory macrophages in adipose tissue and liver. We found that the orphan GPCR Gpr21 was highly expressed in the hypothalamus and macrophages of mice and that whole-body KO of this receptor led to a robust improvement in glucose tolerance and systemic insulin sensitivity and a modest lean phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 35 publications
3
43
2
Order By: Relevance
“…Mice were gavaged with 100 mg/kg Fex or corn oil vehicle daily for 3 weeks before hyperinsulinemic-euglycemic clamp studies. Clamp studies were performed as described 50 . Briefly, dual catheters (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were gavaged with 100 mg/kg Fex or corn oil vehicle daily for 3 weeks before hyperinsulinemic-euglycemic clamp studies. Clamp studies were performed as described 50 . Briefly, dual catheters (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Blood glucose was measured at 0, 15, 30, 60, and 90 min after injection, and blood samples were taken at 0 and 10 min to measure glucose-stimulated insulin secretion. Hyperinsulinemic-euglycemic clamps were performed in the sixth week of iG feeding, as previously described (9,26), to quantitate the degree of systemic and tissue-specific insulin sensitivity. Briefly, dual catheters (MRE-025) were implanted in the right jugular vein, tunneled subcutaneously, and exteriorized at the back of the neck.…”
Section: Methodsmentioning
confidence: 99%
“…In line with these observations, several studies that target ATMs to attenuate the secretion of proinflammatory cytokines have shown beneficial effects with respect to insulin resistance (6,7). Over the last years, several G proteincoupled receptors (GPCRs) have emerged as critical regulators of ATM function (8)(9)(10)(11)(12)(13)(14), rendering them highly attractive as targets for drug development.…”
Section: Introductionmentioning
confidence: 90%